The end of penal populism : the rise of populist politics: Koniec populizmu penalnego i rozkwit polityk populistycznych (Archives of Criminology, 2023)
Penal populism has radically reshaped and reorganised many aspects of punishment in modern society. It has also shifted the emphasis from protecting the rights of individuals from excessive use of the state’s power to punish to using those powers to protect the public from individuals thought to put them at risk. In so doing, it has acted as a kind of dam, holding back the anxieties and uncertainties unleashed by the neo-liberal restructuring of these societies. However, the ascendancy of populist politics indicates that this containment role is ending. The toxic contents that had been stored behind the dam have now spread throughout the social body. This paper argues that the reasons for these developments lie in the effects of the 2008 global financial crisis and the mass movement of people around the globe. As this has occurred, penal populism has taken on a new role. It is incorporated within the broader thrust of populist politics and is used to punish and control its wider sweep of public enemies which it needs to sustain itself.